An annotated checklist of the psyllids of California (Hemiptera: Psylloidea) - Percy, Diana M.; Rung, Alessandra; Hoddle, Mark S. (Zootaxa, 2012)
A revised checklist to the species of Psylloidea (Hemiptera) from California is presented, with information on host plantdata, distributions, introduced and pest species, parasites, parasitoids, and predators, and biological control programs. Thelist includes 164 species, of which six are newly recorded. In total, this comprises a 26% increase in the number of speciesrecorded for California since the last published checklist in 1988. Choricymoza Bliven is a new synonym of PhylloplectaRiley, and 10 species previously in Euphalerus Schwarz are recombined under Nyctiphalerus Bliven. California has therichest native psyllid fauna in North America, and the influence of climatic and floristic diversity on this diversificationis considered. Key words: biogeography, host plant, jumping plant lice, species diversity, pest species.